THE PERFORMANCE OF QUEUE LENGTH OF VEHICLE ON THE ROUNDABOUT AT SELAMAT DATANG MONUMENT USING PTV VISSIM - Harwidyo Eko Prasetyo; Andika Setiawan; Trijeti Trijeti; Tanjung Rahayu; Ayu Ramadhona (International Journal of Civil Engineering and Infrastructure, 2021)
Traffic density or congestion in DKI Jakarta is an issue that difficult to resolved. In this study, an analysis of traffic congestion was carried out by looking at the length of the vehicle queue that occurred at the roundabout. PTV VISSIM performs simulations by entering vehicle volume data and others. The program also shows the results of projections for the next 5 years to find out the impact of traffic at the roundabout. The value of traffic growth per year is 1%. In analyzing the existing conditions using PTV VISSIM, calibration and validation are necessary. On the Jl. Thamrin N-S obtained a queue length of 461.69 m. For sections on Jl. Sudirman S-N is 482.13 m. For the queue length in the existing condition, projections are made for the next 5 years. After the projection, simulation comes with 2 alternatives, road widening and underpass. Based on the projections and alternatives made, the queue length can be obtained. Based on the analysis with these projections and alternatives, the alternative underpass for the queue length on Jl. Thamrin N-S is 0.0 m long and on Jl. Sudirman S-N is 356.20 m. On the Jl. Thamrin N-S is 407.10 m and on Jl. Sudirman S-N is 444.98 m.